Analysis of the RelA:CBP/p300 Interaction Reveals Its Involvement in NF-κB-Driven Transcription - Mukherjee, Sulakshana P.; Behar, Marcelo; Birnbaum, Harry A.; Hoffmann, Alexander; Wright, Peter E.; Ghosh, Gourisankar (PLOS Biology, 2013)
A structural and functional study delineates how the interaction between NF-κB subunit RelA and co-activator CBP/p300 helps drive transcription of NF-κB target genes.